2008
DOI: 10.1002/elps.200700766
|View full text |Cite
|
Sign up to set email alerts
|

Macrocyclic polyamine‐modified poly(glycidyl methacrylate‐co‐ethylene dimethacrylate) monolith for capillary electrochromatography

Abstract: Macrocyclic polyamine-modified poly(glycidyl methacrylate-co-ethylene dimethacrylate) monolith for capillary electrochromatography 1,4,10,13,,17-dione (macrocyclic polyamine)-modified polymer-based monolithic column for CEC was prepared by ring opening reaction of epoxide groups from poly(glycidyl methacrylate-co-ethylene dimethacrylate) (GMA-co-EDMA) monolith with macrocyclic polyamine. Conditions such as reaction time and concentration of macrocyclic polyamine for the modification reaction were optimized to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…It has been reported that the methacrylate-based monolith is highly stable under extreme pH conditions for the analysis of a wide range of compounds [15,16]. But for obtaining the optimal CEC separation conditions of the five vitamin B analytes, the main chromatographic parameters, such as pH and the concentration of the phosphate buffer, should be carefully investigated.…”
Section: Optimizing the Separation Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that the methacrylate-based monolith is highly stable under extreme pH conditions for the analysis of a wide range of compounds [15,16]. But for obtaining the optimal CEC separation conditions of the five vitamin B analytes, the main chromatographic parameters, such as pH and the concentration of the phosphate buffer, should be carefully investigated.…”
Section: Optimizing the Separation Conditionsmentioning
confidence: 99%
“…Among these, the methacrylate-based monolith is the most popular type with fine control of pore characteristics and high stability under extreme pH conditions. Thus, the monolith column is frequently applied in the analysis of a wide range of compounds [15,16]. However, so far to our knowledge, the analysis of vitamin B analytes by CEC has not been explored.…”
Section: Introductionmentioning
confidence: 99%
“…Acrylates and methacrylates represent a very rich family of monomers enabling access to numerous functionalities residing in the ester part of the molecule that are easily copolymerized with a variety of crosslinkers such as ethylene dimethacrylate (EDMA), butanediol diacrylate, and trimethylolpropane trimethacrylate to afford both the desired well‐controlled porous structure and pore surface chemistry. Interestingly, glycidyl methacrylate leads the list of monomers used for the preparation of monolithic capillary columns for CEC 85–90. We have introduced this monomer in the preparation of porous polymer beads already in 1975 91, and the first monoliths consisted of this monomer as well 2, 3.…”
Section: Polymethacrylate Copolymersmentioning
confidence: 99%
“…So far, there have been three different types of organic polymeric monoliths described by various research groups, including acrylate ester-based monoliths [20][21][22][23], acrylamide-based monoliths [24,25] and styrene-based monoliths [26,27]. Whereas most literatures on polymeric monolithic columns in CEC has focused on methacrylate-based monoliths due to their unique properties, such as highchemical stability and excellent mechanical property in a wide pH range [28,29].…”
Section: Introductionmentioning
confidence: 98%